Studi Deskriptif: Sedentary Lifestyle pada Remaja di Era Digital - Syifa Imaniar Rahma; Mamat Lukman; Witdiawati Witdiawati (Malahayati Nursing Journal, 2025)
ABSTRACT The development of technology in the digital era has significantly changed the lifestyle of adolescents, especially in increasing sedentary lifestyle. This lifestyle if ignored will have a negative impact on health. Therefore, it is important to understand the pattern of sedentary lifestyle in adolescents. This study aims to describe the level of sedentary lifestyle in adolescents and analyze the characteristics of respondents who contribute to sedentary time. This study is a quantitative descriptive study with a cross-sectional design. The population of this study were X and XI grade students at SMKN 2 Garut. The sampling technique used stratified random sampling with a sample 220 adolescents. The research tool used the Adolescents Sedentary Activity Questionnaire (ASAQ). Data analysis used univariate analysis which resulted in frequency distribution and percentage. The results of this study showed 86.8% of adolescents had a high sedentary lifestyle, with an average sedentary time reaching 8.3 hours / day. The most sedentary activity is using a computer/laptop/HP for recreation (131.8 minutes/day). Age, gender, and involvement in activities outside of school contributed to the high level of sedentary lifestyle. Adolescents in the digital era tend to have a high sedentary lifestyle, especially the use of digital devices for entertainment and low physical activity exacerbates this condition. Therefore, promotive and preventive efforts such as education and motivation are needed to increase physical activity and the negative impacts of a sedentary lifestyle. Keywords: Adolescent, Digital Era, Sedentary Lifestyle  ABSTRAK Perkembangan teknologi di era digital telah membawa perubahan signifikan terhadap gaya hidup remaja, terutama dalam meningkatkan sedentary lifestyle. Gaya hidup ini jika dibiarkan akan berdampak negative terhadap kesehatan. Oleh karena itu, penting untuk memahami pola sedentary lifestyle pada remaja. Penelitian ini bertujuan untuk mendeskripsikan tingkat sedentary lifestyle pada remaja serta menganalisis karakteristik responden yang berkontribusi terhadap waktu sedentary. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan desain cross-sectional. Populasi penelitian ini merupakan siswa kelas X dan XI di SMKN 2 Garut. Teknik sampling menggunakan stratified random sampling dengan sampel sebanyak 220 remaja. Alat ukut penelitian menggunakan kuesioner Adolescent Sedentary Activity Questionnaire (ASAQ). Analisis data menggunakan analisis univariat yang menghasilkan distribusi frekuensi dan persentase. Hasil penelitian ini menunjukkan 86.8% remaja memiliki sedentary lifestyle yang tinggi, dengan rata-rata waktu sedentary mencapai 8.3 jam/hari. Aktivitas sedentary yang paling banyak dilakukan yaitu menggunakan computer/laptop/HP untuk hiburan (131.8 menit/hari). Faktor usia, jenis kelamin, serta keterlibatan dalam aktivitas di luar sekolah turut berkontribusi terhadap tingkat sedentary lifestyle yang tinggi. Remaja di era digital cenderung memiliki gaya hidup sedentary yang tinggi terutama penggunaan perangkat digital untuk hiburan dan rendahnya aktivitas fisik memperuruk kondisi ini. Oleh karena itu, diperlukan upaya promotive dan preventif seperti edukasi dan motivasi dalam peningkatkan aktivitas fisik dan dampak negative dari gaya hidup sedentary. Kata Kunci: Era Digital, Remaja, Sedentary Lifestyle